Peran Tarekat Naqsyabandiyyah dalam Pembentukan Etika Sosial - Abdillah Rizki Tanjung; Agusman Damanik; Akhmed Syarifatul Raflus; Aldi Firmansyah; Sulistiani Sulistiani; Nurmahmudi Junaid; Ridzky Wahyuni; Sriyanti Sriyanti; Dela Amanda (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
In the dynamics of religious life, Sufi orders, as part of the Sufi tradition, play a significant role not only in spiritual development but also in the formation of social ethics. This study examines the role of the Naqshbandi Order in shaping moral character and social behavior conceptually, based on the Sufi teachings contained within that tradition, using a descriptive qualitative approach through library research. Data were obtained from various relevant primary and secondary literature sources and analyzed using content analysis techniques. This study does not focus on empirical practices in the field, but rather on a normative analysis of the ethical concepts and principles contained in the teachings of the Naqshbandi Order. The research findings indicate that the Naqshbandi Order conceptually embodies ethical values encompassing the cultivation of individual moral character and spirituality, the strengthening of solidarity and social brotherhood, as well as the internalization of values of moderation and social engagement, reinforced by the exemplary conduct and moral authority of the mursyid as the central figure within the order. Thus, the Naqshbandi Order can be understood as a system of teachings with a normative foundation in the formation of social ethics rooted in the spiritual values of Islam.